2017
DOI: 10.1016/j.ymgmr.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of adult patients with inborn errors of metabolism in Spain: A review of 500 cases from university hospitals

Abstract: Patients with inborn errors of metabolism (IEMs) have become an emerging and challenging group in the adult healthcare system whose needs should be known in order to implement appropriate policies and to adapt adult clinical departments. We aimed to analyze the clinical characteristics of adult patients with IEMs who attend the most important Spanish hospitals caring for these conditions. A cohort study was conducted in 500 patients, categorized by metabolic subtype according to pathophysiological classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…As expected, the most frequent disorder was PKU (including hyperphenylalaninemia), representing 23 (18.3%) cases. This frequency is close to the Report of the SSIEM adult Group (20.6%) and a study from Perez-Lopez et al (21.6%) where 500 cases of adult patients with IMD from Reference Centers in Spain were reviewed [12]. The high prevalence of PKU may also be due to the fact that it has been the first disorder included in newborn screening programs [23].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As expected, the most frequent disorder was PKU (including hyperphenylalaninemia), representing 23 (18.3%) cases. This frequency is close to the Report of the SSIEM adult Group (20.6%) and a study from Perez-Lopez et al (21.6%) where 500 cases of adult patients with IMD from Reference Centers in Spain were reviewed [12]. The high prevalence of PKU may also be due to the fact that it has been the first disorder included in newborn screening programs [23].…”
Section: Discussionsupporting
confidence: 84%
“…Firstly, patients with Fabry disease were not included in this study as they were followed at a parallel dedicated clinic. However, previous studies showed that Fabry disease was one of the most prevalent IMD in adults with diagnosis almost exclusively in adulthood [12,18]. This may affect the interpretation of the disease frequencies and age group at diagnosis in our cohort and its comparison with previous studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As expected, the most frequent disorder was PKU (including hyperphenylalaninemia), representing 23 (18.3%) cases. This frequency is close to the Report of the SSIEM adult Group (20.6%) and a study from Perez-Lopez et al (21.6%) where 500 cases of adult patients with IMD from Reference Centers in Spain were reviewed (12). The high prevalence of PKU may also be due to the fact that it has been the rst disorder included in newborn screening programs (23).…”
Section: Comparison Of the Size Of Our Clinic And Its Disease Distribsupporting
confidence: 84%
“…Little is known on long-term outcomes of childhood IMD as many of the " rst survivors" are only now approaching middle age. Exploring the long-term outcomes of these patients is, nonetheless, important from the viewpoint of developing the optimal treatment strategy over a lifetime (12). In order to meet this growing demand, programs with a higher level of formal training in adult IMD are underway in several countries (13) leading to adult metabolic physicians specializing in this new and expanding medical discipline (14).…”
Section: Introductionmentioning
confidence: 99%